Understanding spirituality and the sacred in social work practice: spirited conversations - McVeigh, Mary Jo; Hollier, Joel; Ravulo, Jioji (Routledge, 2025)
"Social work is constantly epistemically evolving and embracing diverse bodies of knowledge to inform its ontology and practice frameworks. Over the years the impact of feminist, post -colonial and queer theory, for example, has broadened the social work lens and invited a welcome departure from dominant Westernized, patriarchal and positivist paradigms. However, the separation of the spiritual realm from case work, clinical, community and group work traditions of social work remained steadfast. The last decade or so has seen forages into the issues of social work and spirituality. This examination into spirituality and social work has shown that for many service-users, spiritual practices (be they religious or non-religious) are important in their lives and their way out of difficulties. Concurrently, relationships between socio-political movements and global religions have grown increasingly complex. To create a truly holistic approach to the needs of service-users it is important that social work policy and practice gives voice to these complexities and understands the place of spirituality within service delivery. This book critically reflects upon and discusses the intersecting role of spirituality in the lives of people who access social work services. By gathering contributions from people with lived experience, practitioners, and academics this book will explore a comprehensive range of issues, opening the area of spirituality to current critical, socio-political and cultural thought. It will be of interest to all social work scholars, students and practitioners"--